FOREIGN DIRECT INVESTMENTS, AS A FACTOR FOR ECONOMIC GROWTH IN ROMANIA - MISZTAL, Piotr (Journal of Advanced Studies in Finance, 2010)
The most important aim of the article is to present the influence of foreign direct investments (FDI) on the economic growth in the Romania in period of 2000-2009. The article consists of two pieces. The first part deals with theoretical analysis of the FDI-led growth hypothesis. Moreover, in this part, there is made a brief overview of empirical researches involving this subject. In the next part of article, there is analyzed the importance of foreign direct investments for economic growth in Romania using the Vector Autoregression Model (VAR). There are estimated elasticity coefficients of gross domestic product (GDP) to changes in gross fixed capital formation, employment, exports of goods and services, and foreign direct investments in Romania on the basis of impulse response function. Then, there is made decomposition of the gross domestic product variance to assess the degree of GDP determination by changes in gross fixed capital formation, employment, exports of goods and services, and foreign direct investments in Romania.